Impacts of Emerging Technologies on Multinational Enterprises: Legal Challenges and Opportunities - Meltem Karatepe Kaya (Sakarya Üniversitesi Hukuk Fakültesi Dergisi/Sakarya Hukuk Dergisi)
This paper examines the application of new technologies in addressing the conventional legal challenges encountered by multinational companies due to the principles of company law. These challenges often give rise to concerns regarding liability in the presence of human rights violations and environmental violations caused by multinational enterprises (MNEs).Governments worldwide are responding by crafting domestic and international regulations aimed at addressing MNEs' transgressions, particularly in the domains of environmental protection and human rights. The European Commission's proposal for a Corporate Sustainability Due Diligence Directive (CSDDD) is a notable example. It mandates comprehensive due diligence measures that transcend geographical boundaries, encompassing every facet of a company's value chain. Nevertheless, while significant, the directive grapples with criticisms surrounding liability resolution.This article takes an innovative approach, seeking solutions within technology. It commences by introducing MNEs elucidating their operation domains and contributions to the global economy. Subsequently, it investigates environmental and human rights transgressions committed by MNEs, unraveling the enduring responsibilities and liabilities inherent to their operations. In doing so, it explores an alternative path forward, one that harnesses technology's transformative potential to address the complex challenges MNEs and countries face in an evolving global landscape.